Elimination of Gas and Particulate Emissions in Coal Boilers using Plasma Precipitator System - Djayanti, Silvy; Suherman, Alex Lukmanto (Makara Journal of Science, 2021)
A plasma precipitator reactor is an essential part of the emission treatment. This device removes fine particles, such as dust, smoke, and various toxic gases, using the force of an induced plasma charge, minimally impeding the flow of gases through the unit. In this study, the plasma precipitator combines dust deposition-capture technology by magnetic force and emission gas removal with plasma. The reactor was successfully fabricated and tested in real-world applications of the textile industry to reduce gas and particulate emissions. Using this reactor, SO2, NO2, CO, and CO2 sulfur dioxide (SO2), nitrogen dioxide (NO2), carbon monoxide (CO), carbon dioxide (CO2) gases turned into more environmentally friendly forms, such as O2, with a decrease of approximately 91.3%, 91.4%, 88.3%, and 89.6% w/w, respectively. Meanwhile, the element and molecular forms, which contain sulfur, carbon, and nitrogen, were deposited as particulates in the electrode channels. Using this technology, the number of particulates decreased up to approximately 93.5% w/w. The plasma precipitator reactor does not require high electricity compared to (conventional) scrubbers that use a blower system. The results indicate that plasma precipitators can be used as an advanced technology to replace conventional gas and particulate emission removal systems from the industries.